Pengaruh Profesionalisme dan Time Budget Pressure Pada Kualitas Audit Dengan Fee Audit Sebagai Variabel Pemoderasi - Cita Dewi, Ayu Alit; Ramantha, I Wayan (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of professionalism and time budget pressure on audit quality with audit fees as moderating variables. This research was conducted at 9 Public Accountant Offices in Bali Province. The number of samples used was 45 respondents. The method of determining the sample is nonprobability sampling with a saturated sample technique. Data collection is done by questionnaire. The analysis technique in this study uses the analysis of Moderated Regression Analysis (MRA). The results of the analysis show that professionalism has a positive effect on audit quality and time budget pressure has a negative effect on audit quality. This study also found that audit fees strengthened the influence of professionalism on audit quality and audit fees weakened the influence of time budget pressure on audit quality. Keywords:  professionalism, time budget pressure, audit fee, and audit quality